Seismic stability of obliquely loaded circular plate anchors. (1st December 2020) - Ganesh, R.; Sahoo, Jagdish Prasad
Abstract: The vertical uplift resistance of obliquely loaded circular plate anchors buried in sand subjected to seismic loadings has been obtained in this paper. The pseudo-dynamic approach based on kinematic theorem of limit analysis has been applied for performing the analysis in which the nonlinear acceleration distributions are incorporated considering standing shear ( S ) and primary ( P ) wave propagations within the soil medium. Results are obtained in terms of seismic uplift factor ( Fγs ) due to soil self-weight component for a wide range of parameters. Through a parametric study, the effects of different parameters including normalized frequencies of Shear ( S ) and Primary ( P ) waves and damping ratio ( ξ ) of soil are highlighted. On account of amplified accelerations effects, the value of F γs has been found to drastically reduce with an increase in load inclination ( θ ), horizontal and vertical seismic acceleration coefficients ( k h and k v ). The results show that the influence of damping ratio ( ξ ) of soil becomes more dominant particularly for frequencies close to the fundamental frequency of P wave. Highlights: Vertical uplift resistance of obliquely loaded circular plate anchors in sand has been obtained under seismic conditions. Pseudo-dynamic approach based on kinematic theorem of limit analysis was applied for performing the analysis. Nonlinear acceleration distributions are incorporated considering standing shear (S) and primary (P) wave propagations. Influence of damping ratio of soil becomes dominant for frequencies close to the fundamental frequency of P wave.